1995
DOI: 10.1021/np50118a020
|View full text |Cite
|
Sign up to set email alerts
|

Patellamide F, a New Cytotoxic Cyclic Peptide from the Colonial Ascidian Lissoclinum patella

Abstract: Cytotoxicity-directed fractionation of an organic extract of the tunicate Lissoclinum patella afforded a new cyclic octapeptide, patellamide F [1]. The structure and absolute stereochemistry of 1 were established by a combination of spectroscopic and chemical methods. Three known cyclic peptides, patellamide B [2], ulithiacyclamide, and lissoclinamide 3, were also isolated and identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 17 publications
1
58
0
1
Order By: Relevance
“…[22][23][24] Oxazoline-, thiazole-, and thiazoline-based cyclic pseudo-hepta-and pseudo-octapeptides, e.g. lissoclinamides, [25][26][27][28][29] patellamides, [30][31][32] and ascidiacyclamide 33,34 can be extracted from L. patella; L. bistratum on the other hand provides oxazoline-based cyclic pseudo-hexapeptides such as westiellamide 35,36 and bistratamide A-H (Scheme 1). 17,[37][38][39][40] In the cyclic peptides, heterocyclic moieties alternate with D-and L-amino acid residues in the peptide sequence.…”
Section: Nina Dovalilmentioning
confidence: 99%
“…[22][23][24] Oxazoline-, thiazole-, and thiazoline-based cyclic pseudo-hepta-and pseudo-octapeptides, e.g. lissoclinamides, [25][26][27][28][29] patellamides, [30][31][32] and ascidiacyclamide 33,34 can be extracted from L. patella; L. bistratum on the other hand provides oxazoline-based cyclic pseudo-hexapeptides such as westiellamide 35,36 and bistratamide A-H (Scheme 1). 17,[37][38][39][40] In the cyclic peptides, heterocyclic moieties alternate with D-and L-amino acid residues in the peptide sequence.…”
Section: Nina Dovalilmentioning
confidence: 99%
“…Independent isolation and anti-HIV activity of 2 were also reported by two other groups [22,23]. A strong cytotoxicity of 2 against the P-388 (leukemia) cell line with an ED 50 of 0.18 mg/mL was reported [20].…”
Section: Minquartynoic Acid and Its Derivativesmentioning
confidence: 66%
“…Different proportions of compound classes are observed within the order Scleractinia (stony corals) where acetogenins slightly dominate over amino acids and isoprenoids [5]. Studies have demonstrated that the genus Tubastraea (order Scleractinia) mainly produces steroids and alkaloids and some are bioactive and toxic to cells [17,18,23,99,100], while others may act against competitors and predators [24,85,101]. According to Lages and collaborators (2012), some of the compounds produced by the invasive species Tubastraea coccinea and T. tagusensis varied in concentration with proximity to the endemic native scleractinian coral Mussismilia hispida and the sponge Desmapsamma anchorata.…”
Section: Natural Products From Cnidariamentioning
confidence: 99%